Pengaruh Sistem Pengendalian Internal Dan Penggunaan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Pada PT.Pelabuhan Indonesia II Persero - Amalia Syafitri; Elsa Meirina (Journal of Creative Student Research, 2023)
This study aims to determine the effect of internal control systems and the use of accounting information systems on the quality of financial reports. The population in this study were all employees at PT.Pelabuhan Indonesia II Persero. The research used a total sampling technique with 40 respondents. The data used is primary data. The data analysis technique used in this research is multiple linear regression using SPSS 22 for windows software. The results showed that the internal control system could not affect the quality of financial reports and the use of accounting information systems had an effect on the quality of financial reports.